(untitled) (Academia Journal of Medicine, 2024)
In recent years, digitization has revolutionized various sectors, with pediatric dentistry being no exception. This review comprehensively summarizes the impacts and advancements of digitization in pediatric dentistry. The utilization of digital technologies has notably enhanced diagnostic accuracy, treatment planning, patient engagement, and educational tools for both dental practitioners and their young patients. Through the integration of digital radiography, intraoral scanning, three-dimensional printing, and teledentistry, the field has seen improvements in patient comfort, reduced procedure durations, and the personalization of dental care. The review aims to highlight the latest developments, potential challenges, and future directions in the digital realm of pediatric dentistry.